The Role of Branding Strategy in Strengthening the Image of the Village Tourism in Bali - Ni Luh Putu Agustini Karta; Ni Made Ary Widiastini; I Ketut Sutapa; Erna Wiles (Jurnal Kajian Bali (Journal of Bali Studies), 2021)
The purpose of this study is to analyze how the tourism village brand strategy in Bali can strengthen the village’s image. The methods are descriptive qualitative (interviews) and quantitative (survey). Eight key informants who are involved in managing the tourism village were interviewed. The sampling technique for the survey was purposive, involving 126 tourists who have visited the tourism villages. Thematic analysis was conducted for the qualitative data; whereas, multiple linear regression was used to analysed the quantitative data. The findings are brand equity and conceptual branding strategy in tourism village have been implemented, however, they need to be optimalized to strengthen the village tourism’s image. The finding from the quantitative data shows that the brand relationship significantly strengthens the image of the tourism village. This research implies that there is a necessity for tourism villages in Bali to design and implement more specific branding methods and set specific purposes so that the new positioning will distinguish them from their competitors and hence, directly strengthen the image.